A clinical audit of Pap smear test for screening of premalignant and malignant cervical lesions - Kumar, Tanya; Aneja, Ankit; Kaur, Satwant; Gulia, Sandhya P. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Cervical cancer, the second most common type of cancer in females, can be easily screened and prevented by Papanicolaou smear test which is a very simple, effective and inexpensive testing modality. The clinical audit aimed to estimate the rate of routine testing as well as the prevalence of various findings of Pap smear tests done at a tertiary level hospital. Methods: It was an analytical cross-sectional study that utilised results of 100 pap smear tests chosen against a set of exclusion and inclusion criteria out of the total 719 pap smears done at Adesh Medical College and Hospital between the duration of 1 January 2022 to 31 May 2022. Results: Only 4.29% of total patients that attended gynaecology OPD got a Pap smear done. A mere 22% patients of those under study came for routine testing. 93% of these 100 patients were negative for intraepithelial lesions, of which 42% were normal, 35% showed non-neoplastic changes and infection was seen in 16% of patients. 7% showed epithelial cell abnormality and 0% had malignant changes. Conclusions: The acceptance of Pap smear for routine screening continues to be low in the Indian setting. There is a massive need to spread awareness among the general public about the importance of Pap smear Test.